2020
DOI: 10.3390/f11121251
|View full text |Cite
|
Sign up to set email alerts
|

Buds, Bugs and Bienniality: The Floral Biology of Eschweilera tenuifolia (O. Berg) Miers in a Black-Water Flooded Forest, Central Amazonia

Abstract: Research Highlights: Our study establishes the biennial nature of flowering intensity as a life-time energy-conserving strategy; we show unexpectedly high flower:fruit ratios despite extensive predation of buds and flowers by insect larvae; ‘selective’ bud abortion may be a key annual energy-saving strategy. Background and Objectives: We aim to explain the strongly biennial flowering pattern of Eschweilera tenuifolia, an ecologically key tree species of Amazon blackwater-flooded forest, inundated for up to nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 113 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Indeed, accessing such supplements from insect larvae may be particularly efficient, since the generally low levels of sclerotization of larval exoskeletons results in their being more easily digested than those of imagoes (Hopkins & Kramer, 1992; Raubenheimer & Rothman, 2013). Furthermore, since infesting larvae are concentrated within the boundaries of the seed, they also represent a clustered resource whose exploitation is more time/energy efficient than the more spatially dispersed adults (Barnett et al, 2020; McNamara & Houston, 1987). This may be significant since, in some fruits, infesting insects can constitute up to 35% of the total mass (Barnett et al, 2022; Barnett, Ronchi‐Teles, et al, 2017; Barnett, Silla, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, accessing such supplements from insect larvae may be particularly efficient, since the generally low levels of sclerotization of larval exoskeletons results in their being more easily digested than those of imagoes (Hopkins & Kramer, 1992; Raubenheimer & Rothman, 2013). Furthermore, since infesting larvae are concentrated within the boundaries of the seed, they also represent a clustered resource whose exploitation is more time/energy efficient than the more spatially dispersed adults (Barnett et al, 2020; McNamara & Houston, 1987). This may be significant since, in some fruits, infesting insects can constitute up to 35% of the total mass (Barnett et al, 2022; Barnett, Ronchi‐Teles, et al, 2017; Barnett, Silla, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many primates, including Chiropotes spp., are also known to eat buds (stem, leaf, and flower) and flowers (Boyle et al, 2012; Di Fiore et al, 2008; Felton et al, 2008; Gregory, 2011; Russo et al, 2005). Given the ubiquity of bud‐borers (Hanover, 1975; Sugiura & Yamazaki, 2009), and the often extensive presence of larval insects in budding and open leaves (Liu et al, 2015), and flowers (e.g., Barnett et al, 2020 for Eschweilera tenuifolia , Lecythidaceae), it is possible that covert carnivory occurs here too. Along with observing insectivory on 18 occasions over a year‐long study of Chiropotes sagulatus , Gregory (2011) observed frequent (101 bouts) consumption of Lecythidaceae flowers, and found that most of the fallen flowers inspected on the ground were infested with a variety of insect larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation